Fertilizer Response of Selected Social Forestry Species under Varying Soil Texture - Mohan, S.; Prasad, K. G.; Gupta, G. N. (Indian Forester, 1990)
Pot culture experiment using sand,loam and clay textured solis was conducted to see the effect of texture and nutrient application (50 ppm each of N, P and K) on Acacia lenticularis, Acacia pJanifrons, Albizia amara, Albizia lebbek, Azaduachta indica, Eucalyptus teretieornis, Hardwickia binata, Peltaphorum pterocarpum and Tamarindus indica. It was observed that A.lebbek, P.pterocarpum and E. tereticornis are highly responsive to clay texture and nutrient application. All species produced higher above and below ground biomass in clay soli except A. amara which produced higher biomass under sandy soil. A.lenticularis, A.amara, A.indica, H.binata and T.indica showed decrease in biomass due to nutrient application. Further studies are suggested.